Dilemmas of mentoring in teacher education: constructing the object - Ottesen, E (2008)
In most countries, teacher education is organised as a joint effort between Higher Education Institutions and local schools. Studies report tensions between the two, often focussing on the so-called theory/practice gap in teacher education. Other studies indicate tensions within the internship, between mentors' roles and responsibilities towards their pupils and their roles and responsibilities as teacher educators. In this paper I use Activity Theory to analyse mentors' and student teachers talk in internship. In internship several needs and motives work on the construction of objects of activity. Based on empirical evidence I identify how pupils' need for continuity and stable routines, the mentors' need to be accountable deliverers of curriculum, and the student teachers need to experiment and try out their ideas may lead to a continuous construction and reconstruction of objects. In earlier work (Ottensen, 2006), I have discussed how mentors' and student teachers' talk is emergent and serendipitous, and that mentors often close rather than expand objects of inquiry. In this paper I investigate objects of inquiry as objects under construction, and show how the mentors' discursive actions connect to the needs and motives of the school, rather than teacher education. In conclusion, I argue that we need to think of internship in teacher education as a design process, paying attention to how objects of inquiry balance motives, promote inspiration, and provide sufficient stability and flexibility (cf. Kaptelinin & Nardi, 2006).